Analisis Proksimat dan Angka Lempeng Total pada Daging dan Tinta Cmi-Cumi (Loligo sp.) dI Pasar Bersehati Manado : Proximate Analysis and Total Plate Count of Squid (Loligo sp.) Meat and Ink at Bersehati Market in Manado City - Taufik, Chesia; Dien, Henny Adeleida; Makapedua, Daisy Monica; Wonggo, Djuhria; Mentang, Feny; Reo, Albert Royke (Sam Ratulangi University, 2026)
Squid (Loligo sp.) has meat that is rich in protein and ink that contains melanoprotein, which is a nutritionally valuable by-product but has not been optimally utilized. This study aimed to analyze the proximate composition (moisture content, ash content, total protein, and total fat) and Total Plate Count (TPC) of fresh squid meat and ink purchased from Bersehati Market, Manado. The study employed a descriptive quantitative method, with proximate and TPC analyses conducted in duplicate using the oven method for moisture content, gravimetric method for ash content, Kjeldahl method for total protein, Soxhlet extraction for total fat, and pour plate method for TPC. The results showed that squid meat had a moisture content of 90.30%, ash content of 1.19%, total protein of 20.05%, and total fat of 0.50%, while squid ink had a moisture content of 83.52%, ash content of 1.69%, total protein of 10.65%, and total fat of 1.66%. Squid meat showed higher moisture content and total protein, whereas squid ink showed higher ash content and total fat. The TPC of squid meat was 1.19 × 10¹ log CFU/mL, while squid ink showed a slightly lower value of 1.09 × 10¹ log CFU/mL, and both squid meat and ink were within the maximum permissible limits of microbial contamination according to the applicable standards. Kata kunci: ink, loligo, meat, proximate, TPC Cumi-cumi Loligo sp. memiliki daging kaya protein dan tinta yang mengandung melanoprotein sebagai limbah bernilai gizi tinggi namun belum dimanfaatkan optimal. Penelitian ini bertujuan untuk menganalisis kandungan proksimat (kadar air, kadar abu, total protein, total lemak) serta Angka Lempeng Total (ALT) pada daging dan tinta cumi segar yang dibeli dari pasar Bersehati Manado. Metode penelitian yang digunakan adalah deskriptif kuantitatif, pengujian proksimat dan ALT dilakukan dengan dua kali ulangan: kadar air (metode oven), kadar abu (gravimetri), total protein (Kjeldahl), total lemak (Soxhlet), ALT (pour plate). Hasil penelitian menunjukkan bahwa daging cumi memiliki kadar air 90.30%, kadar abu 1.19%, total protein 20.05% dan total lemak 0.50%. Tinta cumi memiliki kadar air 83.52%, kadar abu 1.69%, total protein 10.65% dan total lemak 1.66%. Daging cumi memiliki kadar air dan total protein yang tinggi, dan tinta cumi memiliki kadar abu dan total lemak yang tinggi. ALT daging cumi 1.19x101 log CFU/mL, dan tinta cumi sedikit lebih rendah di 1.09x101 log CFU/mL, daging dan tinta cumi masih memenuhi batas maksimum cemaran mikroba sesuai standar yang berlaku. Kata kunci: ALT, daging, loligo, proksimat, tinta